Ethics of Thinking and Habit of Rationalization - Aleksandravičius, Povilas (Problemos, 2016)
In this article, the concept of the ethics of thinking, which has been rarely used previously, is introduced and its basic analysis is carried out. The author claims that this concept corresponds to the understanding of philosophy as spiritual practice, and its essence lies in initiating such a relationship with reality in which “a whole person”, not only the power of conceptual rationality, would be participating. In this light, the philosophy of M. Heidegger, E. Levinas, H. Bergson, S. Weil as well as that of Pope John Paul II – the author of the concept himself, are taken into account. The ethics of thinking is contrasted with the habit of rationalization, which is deeply rooted in the tradition of the European thinking. Rationalization is defined as a replacement of reality by concepts, which ultimately results in the creation of ideologies and their conflicts. A radical phase of rationalization – the global technologisation in which reality has started to be replaced by digits, not by concepts anymore – is singled out. The aim of the article is to juxtapose the two conceptions of thinking in the context of multiple existential problems that the contemporary world is facing.